Self-efficacy and self-care among non-hemorrhagic stroke patients: A cross-sectional study - Priyo Sasmito; Mugi Hartoyo; Treesia Sujana; Sudrajat Sudrajat; Sukirman Lie; Novia Dwi Astuti; Adil Setia Gulo; Ultra Madani; Fahrun Nur Rosyid (Malahayati International Journal of Nursing and Health Science, 2025)
Background:  Self-care is a vital component in the recovery process of non-hemorrhagic stroke patients, who often encounter physical and psychological challenges that reduce their independence. One influential factor in self-care ability is self-efficacy. Purpose: To determine the relationship between self-efficacy and self-care in non-hemorrhagic stroke patients. Method: A descriptive correlational, specially focusing on cross-sectional method. The study took place from December 2023 – December 2024 in Dr. Kariadi General Hospital, Semarang. The independent variable was self-efficacy dependent variable is self-care in non-hemorrhagic stroke patients. Using purposive sampling and lameshow formula 55 participants were selected who met specific inclusion and exclusion criteria. The analysis proceeded with a univariate test to determine the frequency distribution of respondent’s characteristics, followed by bivariate analysis using pearson correlation. Results:  Here strong and statistically significant positive relationship r = 0.698, p = 0.000 between self-efficacy and self-care wiith a mean self-efficacy of 25.57±4.60 and self-care of 56.32±16.8, concluded that greater levels of self-efficacy are significantly correlated with greater self-care ability. Conclusion: The study a significant positive correlation between self-efficacy and self-care in non-hemorrhagic stroke patients, indicating that increased confidence in patients correlates with their ability to engage in self-care independently.